[Professor Samuelson on Free Enterprise and Economic Inefficiency: A Comment]: Reply - Samuelson, Paul A. (Quarterly Journal of Economics, 1970)
Journal Article Professor Samuelson on Free Enterprise and Economic Inefficiency: Reply Get access Paul A. Samuelson Paul A. Samuelson Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 84, Issue 2, May 1970, Pages 341–345, https://doi.org/10.2307/1883021 Published: 01 May 1970